Implementasi Metode Adab Role Playing untuk Meningkatkan Nilai Moral Anak Usia Dini Berbasis Youtube - Cut Citra Novita (Universitas Ngudi Waluyo, 2022)
In the era of the 21st century industrial revolution, technology is not something that children should avoid using, because during the pandemic online learning applies to all schools in all parts of the world. YouTube content is one of the things that are most in demand and liked by children, but not all content on YouTube is educational. Considering that youtube is the social media closest to children, this study designed the use of youtube content with role playing manners to increase children's moral values. Learning is packaged nicely and interestingly, as children like with a duration of broadcast that is appropriate for their age. This research was conducted in the 365 online program, with the subject of children aged 3-4 years. Data collection techniques were taken through observation and documentation. The analysis technique was carried out in a qualitative descriptive manner. This research was successfully carried out to improve moral values in children's daily lives because the method used was designed so that children were easy to understand and apply in a variety of activities.